Detail Desain Saluran Irigasi Di Daerah Kumbung Kecamatan Lunang Kabupaten Pesisir Selatan - Vionadwiuchtia Idrat (Fakultas Teknik Universitas Cenderawasih, 2023)
The effect of water is very large on the agricultural sector, because with sufficient water the needs of plants are fulfilled so that plants can grow well and can increase agricultural yields. One way to meet the water needs of plants is to design irrigation canals properly to avoid water shortages. The irrigation system in the Kumbung area already has a technical irrigation system and the channel planned is an open channel with a trapezoidal cross section. The area of ​​the tertiary plot in the kumbung area was 146.53.